2007
DOI: 10.1097/01.shk.0000239771.10528.d3
|View full text |Cite
|
Sign up to set email alerts
|

Collagenase 2/Matrix Metalloproteinase 8 in Critically Ill Patients With Secondary Peritonitis

Abstract: Secondary peritonitis is an important indication for surgical intensive care admissions, and it is associated with high morbidity and mortality. Collagenase 2/matrix metalloproteinase (MMP) 8 is a tissue matrix-degrading enzyme that is released from leukocytes upon inflammatory stimuli and may thus contribute to peritonitis-associated organ damage. We studied the levels and activity of MMP-8 in the peritoneal fluid of 15 critically ill patients with secondary peritonitis. The MMP-8 levels were measured from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 33 publications
2
17
1
Order By: Relevance
“…The researchers concluded that TIMP-1 might serve as a useful laboratory marker for predicting the clinical outcome for patients with severe sepsis (44). High levels of neutrophil MMP-8 also were found in the peritoneal fluid of critically ill patients with secondary peritonitis (43). By analyzing the expression of some MMP and TIMP genes in livers, kidneys, spleens, and brains of mice at various time points after LPS injection, Pagenstecher's group demonstrated organ-specific and time-specific upregulation of several MMP genes and the TIMP-1 gene (113).…”
Section: Expression Of Mmps During Sepsis and Endotoxemiamentioning
confidence: 99%
“…The researchers concluded that TIMP-1 might serve as a useful laboratory marker for predicting the clinical outcome for patients with severe sepsis (44). High levels of neutrophil MMP-8 also were found in the peritoneal fluid of critically ill patients with secondary peritonitis (43). By analyzing the expression of some MMP and TIMP genes in livers, kidneys, spleens, and brains of mice at various time points after LPS injection, Pagenstecher's group demonstrated organ-specific and time-specific upregulation of several MMP genes and the TIMP-1 gene (113).…”
Section: Expression Of Mmps During Sepsis and Endotoxemiamentioning
confidence: 99%
“…Use of a higher dose regimen may increase the risk of adverse drug effects and antimicrobial resistance. The IFMA method for measuring MMP-8 concentration in serum, although not being a commercially available product, has been successfully used in dental-and sepsis studies [17,20,22]. In a recent study conducted on burn patients using IFMA the healthy controls showed a median plasma MMP-8 concentration of 22.73 (1.66-59.02) ng/ml, whereas in the critically ill patients median MMP-8 was 92.49 (59.62-159.0) [36].…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated based on a previous study on admission MMP-8 -levels in ICU-treated peritonitis patients [20]. Our study was designed to have an 80% power to detect a 50% change in the plasma levels of MMP-8 of doxycycline-treated patients, with a p-value of <0.05 to designate statistical significance.…”
Section: Study Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two recent studies have demonstrated that MMPs are present in the 3rd space fluids of human patients; peritoneal ascites fluid [86] and interstitial fluid collected from cutaneous blisters [87]. Both studies demonstrated that concentration and activity of MMPs in third space fluids correlate directly with the severity of sepsis as well as patient survival.…”
Section: 1 Pleiotropy and The Potential Of Chemically Modified Tetrmentioning
confidence: 99%